PENDAMPINGAN PENDIDIKAN MEMBACA AL-QUR’AN: Studi Kasus TPA Al-Mubtadin Kelurahan Leuwinanggung Kecamatan Tapos Kota Depok - Khotimah, Husnul; Masykur, Asep; Utomo, Budi (Asosiasi Dosen PTKIS Indonesia, 2024)
Assistance in reading the Qur'an has an important role in the spiritual development of Muslims, especially at the level of the Al-Qur'an Education Park (TPA). In this context, assistance in reading the Qur'an at the Al-Mubtadin TPA in Leuwinanggung village is the focus of this service. The purpose of the team is to describe the role of guidance in improving the quality of Qur'an reading education at Al-Mubtadin TPA using iqra' and tahsin methods. Using qualitative methods with a descriptive approach, several systems of data collection, analysis, observation and interpretation produced significant results with increased reading ability, comprehension, and fluency in reading the Qur'an.